Comparative Study and Aerodynamic Analysis of Rectangular Wing Using High-Lift Systems - P. Radha Krishnan; R. Mukesh; Inamul Hasan; P. Booma Devi; Wubetu Amare Alebachew (International Journal of Aerospace Engineering)
High-lift systems are designed to expand the flight envelope and have a most important effect on the size of the wing, economy, and safety of many airliner configurations. Even a small increment of lift using a high-lift system can significantly impact an aircraft’s profitability. The effective design of the airfoil shape with the required aerodynamic performance is still difficult. In the early days, the designs of airfoils were randomly set up and tested in the flow section, and then, the Wright brothers emerged with a cambered section. NACA has provided an appropriate airfoil definition that supports us in making airfoil designs using formulas, not randomly. This paper describes the influence of aerodynamic analysis of wing with flaps at various deflection angles. Aerodynamic variables for the aircraft wing, which is made up of the NACA airfoil 6412 model with and without flaps, have been studied at various angle of attack (AOA) (i.e., -4, -2, 0, 2, 4, 6, 8, 10, 12, and 16) and different Mach number at 0.2, 0.3, and 0.4. Also, the analysis was done for the 15000 ft altitude to check the density effects for the real-time applications. The coefficients of lift and drag are gained by examining the pressure distribution over the surface of the wing. Lift increases as the approach ascends from a low to a high angle of attack, and the most extreme lift is produced at a specific point. After that, when the angle of attack increases further, the drag component increases, so the stall occurs at that point in time. The results showed that the NACA 6412 airfoil obtained the maximum lift at 14°, and the lift value started to decrease. The CFD computations are performed in Ansys Fluent by performing hybrid mesh using ICEM-CFD. The analysis is performed for various configurations of the wing section, and the effects of flow parameters like angle of attack, altitude, and the gap distance between the main wing and slotted flap were compared to identify the better configurations.